ショウド ト オキアミ グン ノ ブンプ シンド トノ カンレン ニ ツイテ - 久保田, 勝彦; クボタ, カツヒコ; Kubota, Katsuhiko (1981)
P(論文) 天空照度とナンキョクオキアミ(Euphausia superba)群の日周鉛直移動との関連を明らかにするため, 南極海において, 1980年1～2月水産庁開洋丸により調査を実施した天空照度と魚群探知機の記録を解析した。照度の最小値は, 00時付近で0～30lx, 日出時(02時18分～03時24分)には90～520lx, 最大値は12時付近で30000～124000lx, 日没時(20時13分～22時47分)には420～80lxを測定した。夜間(18時20分～04時20分), オキアミ群の最大出現頻度は0～20m層に認められ, その頻度は深度とともに減少している。昼間(08時20分～16時20分)における, オキアミ群の最大出現頻度は20～40m層に認められ, 0～20m層および40～60m層ではほぼ同じ値を呈しているが, 40m以深では深度とともに減少している。そして, オキアミ群の日周鉛直移動と照度との間に関係のあることが, 立証された。 In order to study the relation between solar light intensity and vertical distribution of krill swarms, the author examined the records of light intensity measured by a photometer and the images of krill swarms taken through a fish finder on board the KAIYO MARU in the area south of 61°S between 100°E and 120°E during her first antarctic cruise in the 1979-80 season. The krill swarms occurred above the 100m depth. They concentrated in the surface layer above the 20m depth at night between 1820 and 0420 (local time) and in the 20 to 40m depth layer at daytime. The light intensities at sunrise, noon, sunset and midnight were 90 to 520lx, 30000 to 124000lx, 80 to 420lx and 0 to 30lx, respectively. The diurnal migration of krill swarms in relation to the solar light intensity was confirmed. departmental bulletin paper